Type studies confirm that Perenniporia subacida and its four varieties are synonyms - Wang, Zheng-Hui; Wu, Zi-Qiang; Zhao, Chang-Lin (Phytotaxa, 2017)
Perenniporia subacida (Peck) Donk, previously known as Polyporus subacidus Peck (Peck 1885), causes a serious wood rot disease in tropical and temperate forests (Gilbertson & Ryvarden 1987, Ryvarden & Gilbertson 1994, Núñez & Ryvarden 2001, Dai et al. 2002, Decock & Stalpers 2006, Zhao et al. 2013, Ryvarden & Melo 2014). Peck (1885) described this taxon with four varieties, Polyporus subacidus var. stalactiticus Peck, P. subacidus var. tenuis Peck, P. subacidus var. tuberculosus Peck and P. subacidus var. vesiculosus Peck based on different hosts and this species has been transferred into several genera, Poria Pers., Chaetoporus P. Karst, Oxyporus (Bourdot & Galzin) Donk and Perenniporia Murrill (Saccardo 1888, Bondartsev & Singer 1941, Parmasto 1961, Donk 1967).